Penyadapan oleh KPK dalam Perspektif Due Process of Law - Tamara Laurencia (Universitas Medan Area, 2019)
Corruption is very detrimental. KPK was established to eradicate corruption and is given extensive duties and authority. KPK is given the authority to conduct investigation and prosecution, and in the implementation, KPK has the authority to conduct wiretapping. However, the authority given to KPK in conducting wiretapping seems to be too broad and was given without any clear boundaries in terms of the time limit for example. It should also require permission to conduct wiretapping in order to uphold the law. Wiretapping has been a violation of privacy towards citizen rights. The right can only be limited by the Law, but it cannot be removed from existence. One of the principles of criminal procedure in Indonesia is due process of law that consist of three important aspects, namely presumption of innocence, equality before the law, and the rule of law. This principle basically requires the protection of the rights of the suspects or defendants in terms of the substance of the law that regulates or the implementation, which in this case is not to be considered guilty during criminal justice process, equality before the law regarding the right to privacy that can only be limited, not removed from existence.